Feeling Touched: Empathy Is Associated With Performance in a Tactile Acuity Task - Schaefer, Michael; Joch, Marcel; Rother, Nikolas (Frontiers in Human Neuroscience, 2021)
The concept of empathy describes our capacity to understand the emotions and intentions of others and to relate to our conspecifics. Numerous studies investigated empathy as a state as well as a stable personality trait. For example, recent studies in neuroscience suggest, among other brain areas such as the insula or the ACC, a role of the somatosensory cortices for empathy (e.g., when observing someone else being touched). Since the classic understanding of the primary somatosensory cortex is to represent touch on the body surface, we here aimed to test whether tactile performance is linked to the personality trait empathy. In order to test this we examined tactile acuity of 95 healthy participants (mean age 31 years) by using a 2-point discrimination threshold task at the index fingers. Trait empathy was assessed by employing the Interpersonal Reactivity Index (IRI), which measures self-reported empathy with four scales (empathic concern, perspective taking, fantasy, and personal distress). Results of regression analyses suggested the subscale empathic concern to be positively associated with performance in the tactile acuity task. We discuss this finding in the light of recent studies on empathy and consider implications of a possible training to enhance empathy.